1994
DOI: 10.1007/bf00033893
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation in cardenolide biosynthesis

Abstract: The glycosylation and deglycosylation of cardiac glycosides was investigated using cell suspension cultures and shoot cultures, both established from Digitalis lanata EHRH. plants, as well as isolated enzymes. Shoots were capable of glucosylating digitoxigenin, evatromonoside, digiproside, glucodigitoxigenin and digitoxin. Suspension cultured Digitalis cells glucosylated all the substrates mentioned but digiproside, whereas the UDP-glucosedependent cardenolide glucosyltransferase isolated from that source did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Formation of the butenolide ring (117) has been suggested to involve transfer of a malonyl moiety to the 21-hydroxy group to form a malonyl hemi-ester (116) (catalysed by malonyl-coenzyme A: 21-hydroxypregnane 21-hydroxy-malonyltransferase) and subsequent Claisen-type condensation of the malonyl moiety with the C-20 ketone, accompanied by decarboxylation 1224 (rather than Claisen-type condensation as the initial step, as previously assumed). Enzymes involved in the final glycosylation stage have been described from Digitalis species 1225,1226 and Nerium oleander. 1227 The biosynthesis of 5 -cardenolides in Asclepias curassavica has also been studied [1228][1229][1230] and the topic of cardenolide biosynthesis has been reviewed.…”
Section: Biosynthesis Of Plant Steroids and Triterpenes As Secondary ...mentioning
confidence: 99%
“…Formation of the butenolide ring (117) has been suggested to involve transfer of a malonyl moiety to the 21-hydroxy group to form a malonyl hemi-ester (116) (catalysed by malonyl-coenzyme A: 21-hydroxypregnane 21-hydroxy-malonyltransferase) and subsequent Claisen-type condensation of the malonyl moiety with the C-20 ketone, accompanied by decarboxylation 1224 (rather than Claisen-type condensation as the initial step, as previously assumed). Enzymes involved in the final glycosylation stage have been described from Digitalis species 1225,1226 and Nerium oleander. 1227 The biosynthesis of 5 -cardenolides in Asclepias curassavica has also been studied [1228][1229][1230] and the topic of cardenolide biosynthesis has been reviewed.…”
Section: Biosynthesis Of Plant Steroids and Triterpenes As Secondary ...mentioning
confidence: 99%
“…[5,21,29] Most cardiac glycosides embrace one to four sugar residues connected to the genin, increasing their capability to bind to the heart muscle and make them water-soluble. [30,31] Numerous distinct substitution patterns were discovered at the sugar moiety in the calotropis family [Figure 3]. The hydroxyl group can be altered by being acetylated or epimerized at C-3′ and subjected to its oxidation.…”
Section: Insight Into Calotropin's Fundamental Chemical Structurementioning
confidence: 99%
“…The reason for this may be due to its being a double sugar that disintegrates during the process of sterilizing the food medium containing it into two units of Glucose sugar, and as it is known that glucose sugar enters into the formation of primary cardiac glycosides such as Lanatoside C, Lanatoside B, and Lanatoside A, which in turn are converted during the drying process of plant parts to Digoxin, Gitoxin, Digitoxin respectively [16]. For this reason, it was observed that the presence of Maltose sugar in the food medium had the greatest effect on the formation of cardiac glycoside compounds.…”
Section: Maltose Con Gl -1mentioning
confidence: 99%